Individualized teaching modules to develop four reading comprehension skills among fourth-year high school students of vocational and technical schools - Gillera, Caridad Collantes 1941- (1979)
This study provided some instructional materials to develop reading comprehension skill among fourth-year high school students in vocational and technical schools. It also focused its attention on modularized instruction as adaptable in fostering comprehension skills in all subject areas and in all grade levels.
"May, 1979."
Vita.
Thesis (M.A.T. : Reading)--University of the Philippines, Diliman.
Keywords: Individualized reading instruction -- Philippines -- Cebu; Reading comprehension -- Study and teaching (Secondary) -- Philippines -- Cebu